(untitled) (Applied Biological Research, 2023)
The aim of present study was to assess the cytotoxic and genotoxic potency of lead acetate using an Allium root tip bioassay. Root tips of Allium cepa L. were treated with different concentrations of lead acetate viz., 0.03, 0.06, and 0.09 mg mL-1 of lead acetate for 48 h. Mitotic index (MI), phase index (PI), and total chromosomal abnormalities (TA) were calculated. The effect of lead acetate was found to be dose-dependent. The frequency of MI ranged from 8.4 to 5.7%, PI of prophase from 4.2 to 3.4%, PI of metaphase from 1.14 to 1.11%, PI of anaphase from 1.8 to 0.6%, and PI of telophase from 1.1 to 0.4%. The total chromosomal abnormality (TA) ranged from 0.42 to 1.39%. The differences between the averages of all the studied properties were significantly affected by the heavy metal lead acetate concentration variant applied. Mitotic observation showed that increasing of concentration variants doses decrease mitotic index and increased chromosomal abnormality percentage. Various types of physiological and clastogenic (laggard, stickiness, abnormal metaphase, chromatin bridge, and delayed anaphase were observed in Allium cepa root tip cells. Moreover, the A. cepa root tibioassay method gives critical data for evaluating an agent’s action mechanisms and impacts on genetic material.